Rituximab versus natalizumab, fingolimod, and dimethyl fumarate in multiple sclerosis treatment. Issue 9 (6th August 2020) - Vollmer, Brandi L.; Nair, Kavita; Sillau, Stefan; Corboy, John R.; Vollmer, Timothy; Alvarez, Enrique
Abstract: Introduction: Limited comparative effectiveness data for rituximab (RTX) versus natalizumab (NTZ), fingolimod (FTY), and dimethyl fumarate (DMF) for the treatment of multiple sclerosis (MS) exist. Methods: Clinician‐reported data on patients prescribed RTX, NTZ, FTY, or DMF for the treatment of MS at the Rocky Mountain MS Center at the University of Colorado were retrospectively collected. Outcomes included a composite effectiveness measure consisting of clinical relapse, contrast‐enhancing lesions, and/or new T2 lesions, individual effectiveness outcomes, and discontinuation. Logistic regression was used on patients matched by propensity scores and using average treatment effect on treated doubly robust weighting estimator. Results: A total of 182, 451, 271, and 342 patients initiated RTX, NTZ, FTY, and DMF and were followed for 2 years. Before and after adjustment, the odds of experiencing disease activity was significantly higher for FTY [adjusted OR (aOR) = 3.17 (95% CI: 1.81–5.55), P  < 0.001].and DMF [aOR = 2.68 (95% CI:1.67–4.29), P  < 0.001], and similar for NTZ [aOR = 1.36 (95% CI:0.83–2.23), P  = 0.216] versus RTX. When examining months 6–24, NTZ demonstrated higher odds of disease activity compared to RTX [aOR = 2.21 (95% CI: 1.20–4.06), P  = 0.007]. Similar odds of discontinuation were seen between NTZ and RTX [aOR = 1.39 (95% CI: 0.88–2.20), P  = 0.157]; however, FTY [aOR = 2.02 (95% CI: 1.24–3.30), P  = 0.005] and DMF [aOR = 3.27 (95% CI: 2.15–4.97), P  < 0.001] had greater odds of discontinuation than RTX. Interpretation: RTX demonstrated superior effectiveness and discontinuation outcomes compared to FTY and DMF. Although RTX demonstrated similar effectiveness and discontinuation compared to NTZ, RTX had superior effectiveness during months 6–24 and fewer discontinuations when excluding discontinuations due to insurance issues. Results suggest superiority of RTX in reducing disease activity and maintaining long‐term treatment in a real‐world MS cohort.